Avaliação do possível efeito ansiolítico em ratos e camundongos do óleo essencial de Lavandula angustifolia Mill - Fassin Junior, Jaime [UNIFESP] (2010)
The essential oils can be therapeutically used in the control of emotions, for its sedative and anxiolytic effects. On the other hand, the relation between the odor’s perception and the change on the emotional response has been proposed, once their acting on the limbic system has been known as fact. Considering that in popular medicine certain Lavandula essential oils’ depressor properties are proposed, in the present study it was evaluated the possible anxiolytic effects of the same. Methods: 3-5 months old Wistar rats were divided in controlled groups and LEO (2,5%; 100% p/v), being exposed to the inhalation for 7 minutes. The animals were evaluated in the open field, social interaction and elevated plus maze. Results: The results indicate a possible depressor effect for the LEO, suggesting an anxiolytic effect which can be correlated to the communication between the olfactory system and the limbic areas. The regions control the emotions and the animals’ motivation.